Exporting a bit faster: The long-run performance of born globals in computing - Shon Ferguson; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2018)
Policymakers in several countries have recently taken steps to promote the rapid export expansion of high-tech small- and medium-sized enterprises (SMEs). The goal of these policies has been to create successful export-intensive firms, which are often referred to as born globals. To the best of our knowledge, we are the first to study born globals in computing using firm-level register data, which cover the universe of firms in a particular country and sector. Using data on all Swedish computing startups founded 2007-2015, we find a systematic positive relationship between the propensity of a computing firm to reach customers globally via digital platforms and its long-run employment growth relative to domestically-oriented computer firms. We find mixed evidence that born globals in computing grow faster in terms of sales or value added. Our analysis also indicates that very few computing firms fit the profile of born globals; only 15 percent of the 250 largest computing employers in 2015 were born globals. Moreover, only 1.5 percent of computing startups founded 2007-2015 were computer game publishers, which arguably have the highest propensity to be born global. Thus, although we find positive born global effects at the firm level, policymakers must be aware that encouraging more born globals need not necessarily lead to large benefits for the overall economy.
Keywords: F14; F23; L25; M13; 330; Born globals; Computing industry; Exporting; Firm growth; Globalization; Job creation